Ben-Hur (2016) [videorecording (DVD)] - Huston, Jack, 1982-; Kebbell, Toby; Santoro, Rodrigo, 1975-; Freeman, Morgan; Wallace, Lew, 1827-1905 (Paramount, 2016)
The epic story of Judah Ben-Hur, a prince falsely accused of treason by his adopted brother, an officer in the Roman army. After years at sea, Judah returns to his homeland to seek revenge, but finds redemption.